The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/cli8100103
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Satellite-Based Rainfall Products over Nigeria

Abstract: Understanding the variability of rainfall is important for sustaining rain-dependent agriculture and driving the local economy of Nigeria. Paucity and inadequate rain gauge network across Nigeria has made satellite-based rainfall products (SRPs), which offer a complete spatial and consistent temporal coverage, a better alternative. However, the accuracy of these products must be ascertained before use in water resource developments and planning. In this study, the performances of Climate Hazards Group Infrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
5
18
0
Order By: Relevance
“…For instance, in the Central African region (Figure 2a), there is a fairly good agreement in the observed mean daily precipitation from CPC (3.87), CHIRPS (4.21) and TAMSAT (4.38). Even though these values are close, the differences in the products have been observed in other studies (Dinku et al, 2018; Ogbu et al, 2020). There is also a possibility for pronounced variation at the local scale (Fekete et al, 2004).…”
Section: Resultssupporting
confidence: 72%
“…For instance, in the Central African region (Figure 2a), there is a fairly good agreement in the observed mean daily precipitation from CPC (3.87), CHIRPS (4.21) and TAMSAT (4.38). Even though these values are close, the differences in the products have been observed in other studies (Dinku et al, 2018; Ogbu et al, 2020). There is also a possibility for pronounced variation at the local scale (Fekete et al, 2004).…”
Section: Resultssupporting
confidence: 72%
“…The CHIRPS dataset was acquired through the website (http://chg.geog.ucsb.edu/data/chirps/, accessed, February 15, 2021) for the years 1981-2017. The CHIRPS precipitation data was applied in our analysis given that it has been shown to perform better than other satellite products over Africa [43,44] and to be less affected by variation in elevation [45,46].…”
Section: Rainfall Estimatesmentioning
confidence: 99%
“…We obtained daily precipitation rasters for Africa 42 from the Climate Hazards Infrared Precipitation with Stations (CHIRPS) project; this dataset is based on combining sparse weather station data with satellite observations and interpolation techniques, and is designed to support hydrologic forecasts in areas with poor weather station coverage (such as tropical West Africa) 42 . A recent study ground-truthing against weather station data showed that CHIRPS provides greater overall accuracy than other gridded precipitation products in Nigeria 43 . Air temperature daily minimum and maximum rasters were obtained from NOAA and were also averaged to calculate daily mean temperature.…”
Section: Methodsmentioning
confidence: 99%